Enhanced Reality Showing Long-Lasting Analgesia after Total Knee Arthroplasty: Prospective, Randomized Clinical Trial. Issue 1 (December 2018) - Koo, Kyo-in; Park, Dae; Youm, Yoon; Cho, Sung; Hwang, Chang
Abstract To overcome the limitation of short-term efficacy of virtual reality (VR), an enhanced reality (ER) analgesia, (combination of the VR, real-time motion capture, mirror therapy [MT]) involving a high degree of patients' presence or embodiment was explored. Patients, who underwent unilateral total knee arthroplasty (TKA), received ER analgesia. The duration was 5 times a week, for 2 weeks for one group and 5 times a week, for 1 week in the other. Visual Analogue Scale (VAS) at rest and during movement, active knee range of motion (ROM) for flexion and extension were measured repeatedly. After screening 157 patients, 60 were included. Pre-interventional evaluation was performed at 6.7 days and ER was initiated at 12.4 days after surgery. Evaluation was performed at 5, 12, 33 days after the initiation of ER. Analgesia in the 2 week therapy group was effective until the third evaluation (p = 0.000), whereas in the other group, it was effective only until the second evaluation (p = 0.010). Improvement in ROM in the 2 week group was also maintained until the third evaluation (p = 0.037, p = 0.009). It could lay the foundations for the development of safe and long-lasting analgesic tools.